Genome-wide identification of new reference genes for RT-qPCR normalization in CGMMV-infected Lagenaria siceraria - Chenhua Zhang; Hongying Zheng; Xinyang Wu; Heng Xu; Kelei Han; Jiejun Peng; Yuwen Lu; Lin Lin; Pei Xu; Xiaohua Wu; Guojing Li; Jianping Chen; et al. (PeerJ, 2018)
Lagenaria siceraria is an economically important cucurbitaceous crop, but suitable reference genes (RGs) to use when the plants are infected by cucumber green mottle mosaic virus (CGMMV) have not been determined. Sixteen candidate RGs of both leaf and fruit and 18 candidate RGs mostly from separate RNA-Seq datasets of bottle gourd leaf or fruit were screened and assessed by RT-qPCR. The expression stability of these genes was determined and ranked using geNorm, NormFinder, BestKeeper and RefFinder. Comprehensive analysis resulted in the selection of LsCYP, LsH3, and LsTBP as the optimal RGs for bottle gourd leaves, and LsP4H, LsADP, and LsTBP for fruits. LsWD, LsGAPDH, and LsH3 were optimal for use in both leaves and fruits under the infection of CGMMV. Isopentenyl transferase (IPT) and DNA-directed RNA polymerase (DdRP) were used to validate the applicability of the most stable identified RGs from bottle gourd in response to CGMMV. All the candidate RGs performed in RT-qPCR consistently with the data from the transcriptome database. The results demonstrated that LsWD, LsGAPDH and LsH3 were the most suitable internal RGs for the leaf, and LsH3, LsGAPDH, LsP4H and LsCYP for the fruit.